2004
DOI: 10.2116/analsci.20.1363
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Enhancement in Flame Atomic Absorption Spectrometry for Determination of Copper in Human Thyroid Tissues

Abstract: Various designs of quartz tube in a slotted tube atom trap were examined for improving the sensitivity of flame AAS. A 3.5-fold enhancement in the sensitivity was obtained by using the optimized method. The method was applied to the determination of Cu in cancerous and non-cancerous human thyroid tissues. The Cu concentrations of the cancerous samples tended to increase compared with the non-cancerous samples. Zn concentrations of the same tissues were also determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Uda et al observed that the defi ciency or excess of trace elements concentrations in cancerous tissues of different organs may be different (11). In the literature, it is described that trace element concentrations of healthy adult thyroid glands were not dependent on sex or age (12). In our series all of the patients and healthy controls were females and there was no statistical difference between the groups (p>0.05).…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Uda et al observed that the defi ciency or excess of trace elements concentrations in cancerous tissues of different organs may be different (11). In the literature, it is described that trace element concentrations of healthy adult thyroid glands were not dependent on sex or age (12). In our series all of the patients and healthy controls were females and there was no statistical difference between the groups (p>0.05).…”
Section: Discussionmentioning
confidence: 38%
“…In opposite to our results Reddy et al (16) have reported lower levels of Cu in the tissue of cancerous thyroid than in normal thyroid tissue and like our results (our results are refl ecting serum levels), much lower levels of Cu in the tissue of thyroid adenoma. Other authors have estimated the concentration rates of Cu/Zn in the cancerous thyroid tumour were signifi cantly higher than in the normal and other thyroid disease (12,17,18).…”
Section: Discussionmentioning
confidence: 93%
“…Small amount of copper is found in the human body (50-120 mg), but it plays a critical role in a variety of biochemical processes (Yaman and Akdeniz 2004). Copper forms part of at least 13 different enzymes, and its presence is It is known that copper may be toxic to both humans and animals when its concentration exceeds the safe limits (Gast et al 1988).…”
Section: Resultsmentioning
confidence: 99%
“…However, skeletal and reproductive effects are also discussed as possible critical effects (Nordberg 2003). Also, it is known that Cu is essential element yet it may be toxic to both humans and animals when its concentration exceeds the safe limits and its concentration in some human tissues such as thyroid can be change dependent on the tissue state including cancerous or non-cancerous (Yang et al 2002;Yaman and Akdeniz 2004). Obviously, the monitoring of lead, cadmium and copper levels in the environment has a high importance.…”
Section: Introductionmentioning
confidence: 99%